(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This work shows the results of the experiences in pedagogical practices of the students enrolled in the mathematics major at the Pedagogical and Technological University of Colombia. These experiences were developed in the elective course Universal Design for Learning - DUA and through the practice of inclusive education, and they were carried out in different institutions located in the municipality of Duitama, Boyacá. The purpose was to strengthen the pedagogical practices of teachers in training who, due to the COVID-19 pandemic, had to cut short their first experiences in the classroom. The methodology was based on the observation and characterization of each educational space, the strategy designs based on the DUA, the implementation of these strategies in the classroom, and finally, the collection and qualitative analysis of this data. The conclusion is that the DUA approach brings forth innovation in teaching processes, eliminates barriers, and strengthens educational practices.